Minat Siswa Berlatar Belakang Non Madrasah Dengan Sekolah Dasar Dalam Belajar Bahasa Arab Di Madrasah Tsnawiyah Islamiyah Palangka Raya - Mirza Mahfud; Nurul Wahdah; Marsiah Marsiah (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2023)
This study aims to determine the comparison of learning interest in learning Arabic among students with an educational background in Madrasah Ibtidaiyah and Elementary Schools. The population in this study were students of grades VIII and IX at MTs Islamiyah Palangka Raya, totaling 123 students. The sample of this study consisted of 60 students, which was divided into 2 which resulted in 30 students from Madrasah Ibtidaiyah and 30 students from Elementary Schools by determining the number of sample members by Quotum or rations. Data collection techniques in this study were observation, documentation methods, interview methods (interviews), questionnaires (questionnaires), while the research instruments were using validity tests and data reliability tests. The data analysis method in this study is a quantitative analysis method using a questionnaire method which is used to find out the comparison of the interests of students with an educational background in Madrasah Ibtidaiyah and Elementary Schools. The results of this study indicate that the interest in learning Arabic between Madrasah Ibtidaiyah alumni and Elementary School alumni is actually higher for Madrasah Ibtidaiyah alumni than Elementary School alumni, namely from the results of the normality test and homogeneity test, and a T test is carried out (see; Normality Test table, Homogeneity and Independent Tests), also from the results of the Group Statistics table that the average results of the MTs alumni questionnaire = 70.7667 and the average results of the SMP alumni questionnaire = 60.9000, with reference to 4 aspects, namely aspects of motivation, participation, attention and responses, as well as seen from the factors that influence the emergence of interest in both.